Heritable Heaven: Erotic Properties in the Dickinson-Lord Correspondence - JAMES GUTHRIE (Reading Emily Dickinson's Letters, 2009)
The drafts of letters Emily Dickinson apparently wrote during her correspondence with Judge Otis Phillips Lord, justice of the Massachusetts Supreme Court, employ a wide range of legal terms and references. Elsewhere I have discussed the extent to which the drafts dwell upon matters related to property law, notably the areas of bankruptcy and trespass, as part of a larger campaign Dickinson conducted to negotiate the conditions of their romantic relationship.¹ I wish to expand upon that subject now by considering how her correspondence with Judge Lord makes similar use of concepts drawn from the practice of estate law. Although